2018
DOI: 10.1007/s10758-018-9352-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Software, Task Solving With or Without Guidelines, and Learning Outcomes

Abstract: The present study contributes to knowledge about how to design tasks that benefit from dynamic software in math education, comparing practice performance and learning outcomes among 129 students practicing on two different task designs using GeoGebra. The task designs differed with respect to the presence or absence of guidelines on how to solve the task. One student group practiced on the guided task while the other student group practiced on the unguided task, and 1 week later a posttest was conducted. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…Several previous studies [10], [11], [26], [27], [30]- [32] have focused on using GeoGebra in mathematics learning from elementary school to university. A study conducted by Khalil et al [33] showed that the use of GeoGebra in learning analytical geometry in high schools had a significant positive effect on students' abilities compared to students who traditionally studied using paper and pencil.…”
mentioning
confidence: 99%
“…Several previous studies [10], [11], [26], [27], [30]- [32] have focused on using GeoGebra in mathematics learning from elementary school to university. A study conducted by Khalil et al [33] showed that the use of GeoGebra in learning analytical geometry in high schools had a significant positive effect on students' abilities compared to students who traditionally studied using paper and pencil.…”
mentioning
confidence: 99%
“…Olsson and Granberg [22] describe the benefits of using dynamic software, such as GeoGebra, which will allow students to work with unguided tasks (tasks that do not have a defined outcome), which is the case in the architectural modelling practices. However, they propose that some challenges have to be met to ensure the success of such unguided tasks using dynamic software.…”
Section: Geogebraa Problem-solving Instrumentmentioning
confidence: 99%
“…1) in this study was based on these principles. It was used in our earlier studies (Granberg 2016;Olsson 2018;Olsson and Granberg 2018) and was designed for users with limited experience with GeoGebra. It was shown that they could receive guidance with respect to how to enter algebraic expressions into GeoGebra and in how to use the angle-measuring tool combined with instructions to focus on m-values (the x-coefficient) and test the solution, but still have to construct parts of the solution themselves.…”
Section: Design Of the Tasksmentioning
confidence: 99%
“…Task 2 (see Fig. 2) was originally designed for a quantitative study comparing learning outcomes of Tasks 1 and 2 with respect to the characteristics of reasoning (Olsson and Granberg 2018). It was designed based on Lithner's (2017) principle for AR tasks, providing a task-solution method.…”
Section: Design Of the Tasksmentioning
confidence: 99%
See 1 more Smart Citation